Auricular vagus nerve stimulation promotes functional recovery and enhances the post-ischemic angiogenic response in an ischemia/reperfusion rat model. (July 2016) - Jiang, Ying; Li, Longling; Ma, Jingxi; Zhang, Lina; Niu, Fei; Feng, Tao; Li, Changqing
Abstract: Electrical stimulation of the vagus nerve, which has been used to treat epilepsy patients since 1997, also enhances long-term restoration after central nervous system (CNS) injury. Angiogenesis is a complex restorative mechanism that occurs in response to ischemic stroke, and it positively affects the recovery of neurological functions in a rat model of stroke. The aims of our study were to determine whether auricular vagus nerve stimulation (aVNS) promoted functional recovery and enhanced angiogenesis in the ischemic boundary following ischemia/reperfusion and to uncover the possible molecular mechanisms that are involved. Adult male Sprague-Dawley (SD) rats underwent transient middle cerebral artery occlusion (tMCAO) surgery and received repeated electrical stimulation of the left cavum concha starting 30 min after ischemia. For the following 21 days, we evaluated functional recovery at different time points using neurological deficit scores, the beam-walking test and the staircase test. The infarct volume was measured using TTC staining at 24 h post reperfusion, neuronal survival in the ischemic penumbra was assessed using hematoxylin and eosin (HE) staining. Microvessel density and endothelial cell proliferation in the ischemic boundary were assessed using immunofluorescence. The expression levels of brain-derived neurotrophic factor (BDNF), endothelial nitric oxide synthase (eNOS) and vascular endothelial growth factor (VEGF) in the ischemic penumbra were also evaluated. Our results showed that aVNS had significant neuroprotective effects and enhanced angiogenesis, which was demonstrated by improvements in the behavioral scores and brain histopathology, including increased levels of microvessel density and endothelial cell proliferation surrounding the infarct area. Furthermore, BDNF, eNOS and VEGF were expressed at higher levels in the I/R + aVNS group than in the I/R group or the I/R + sham aVNS group (p < 0.05). Our findings suggest that repeated aVNS promoted post-ischemic functional recovery and angiogenesis, possibly in conjunction with the up-regulated expression of BDNF, eNOS and VEGF in the rat brain. Highlights: aVNS improves functional recovery in stroke rats. aVNS increased BDNF, p-eNOS and VEGF expression in rat model of ischemia/reperfusion. The neuroprotection induced by aVNS might be closely associated with enhancement of postischemic angiogenesis process.